Modelling Inclusiveness of Growth in Nigeria. What are the Roles of Remittances and Institutional Quality? Array - Ogede, Jimoh Sina (The Journal of Accounting and Management, 2020)
The Nigerian economy has witnessed tremendous growth in the last three and half decades, yet 62.7% of the 188 million population remains poor. The non-inclusiveness of growth recorded has heightened the search for the underlying cause of this age-old macroeconomic problems. The institutional mechanism in place to attract worker’s remittances in order to attain a broad-based growth have been the placed at the forefront of the national quest for growth to be inclusive. In analysing the role of institutions in the remittance-inclusive growth puzzle, this paper employ the Auto-Regressive Distributed Lag Approach to account for the short-run and long-run structural properties of the model. Findings reveals that remittances has a long-term negative relationship with inclusiveness of growth while institutional quality positively enhances inclusiveness of growth in Nigeria in the long-run. However, institutions have negative short-term relationship with inclusive Growth while remittances have short-term positive relationship with inclusive Growth in Nigeria. It is therefore recommended that the society should do more to embrace strong institutions that will promote inclusiveness and their instrumental value as a means toward better growth performance and equal income distribution.